Fostering Moral Education Through the Habituation of the Seven Sunnahs of Prophet Muhammad at Madrasah Tsanawiyah - Rudi Ahmad Suryadi; Muhtar Jarkasih; Nazelina Salsabila Putri; Elit Fuziawati (STAI Hubbulwathan Duri, 2025)
Moral decline among students highlights the urgent need for character education rooted in Islamic values. This study examines the habituation process of the seven Sunnahs of the Prophet Muhammad at MTs Akhlaqiyah and its role in moral education. A descriptive qualitative approach with a case study design was employed. Data were collected through observations, interviews, documentation, and questionnaires. Validation was ensured through triangulation and extended observations, and data were analyzed using collection, reduction, and conclusion-drawing techniques. The findings reveal the structured habituation of the seven Sunnahs, including Tahajjud and Dhuha prayers, murojaah (Qur'an recitation), dhikr (remembrance of Allah), maintaining ablution, charity, and congregational prayers. While Tahajjud is performed outside of school, other activities are well-facilitated within the institution. This habituation program has significantly improved students' time discipline, honesty, social awareness, responsibility, and respect for teachers and parents. The structured implementation of these religious practices fosters positive behavioral change and strengthens students' moral character. By integrating Islamic teachings into daily routines, the program enhances spiritual discipline and ethical awareness, preparing students to navigate moral challenges in contemporary society. The habituation of the seven Sunnahs effectively shapes students' character in alignment with Islamic values. This study underscores the importance of integrating religious practices into educational frameworks to cultivate a morally upright generation. Future research should explore long-term impacts and potential scalability to other educational institutions.